Upaya Pelestarian Musik Daerah Talempong Batuang dari Silungkang Oso Kota Sawahlunto Melalui Film Pendek Dokumenter - Akbar, Fino Aidil; Najmi, Maisaratun (Asosiasi Ide Bahasa Kepri, 2024)
This research examines the preservation of the traditional talempong batuang musical instrument through documentary films as part of efforts to preserve cultural heritage. Talempong batuang, a melodious percussion instrument typical of Silungkang, Sawahlunto, was recognized as Indonesia's intangible cultural heritage in 2023 after going through a long nomination and verification process. By using a research approach carried out in the creation of documentary films based on communication theory and social change based on Marshall McLuhan's theory, this research analyzes how documentary films become an effective vehicle for recording, educating and spreading the cultural values ​​of Talempong Batuang. The results show that documentary films not only function as visual archives but also as a way of preserving culture, making it an appropriate conservation strategy in facing the challenges of modernization. This study recommends collaboration between cultural actors, policy makers and filmmakers to develop other local traditions through documentary films.